1994
DOI: 10.1073/pnas.91.25.12273
|View full text |Cite
|
Sign up to set email alerts
|

Chemiluminescent activation of the antiviral activity of hypericin: a molecular flashlight.

Abstract: Hypericin is a naturally occurring photosensitizer that displays potent antiviral activity in the presence of light. The absence of light in many regions of the body may preclude the use of hypericin and other photosensitizers as therapeutic compounds for the treatment of viral infections in vivo. The chemiluminescent oxidation of luciferin by the luciferase from the North American firefly Photinus pyralis was found to generate sufficiently intense and long-lived emission to induce antiviral activity of hyperi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
89
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(91 citation statements)
references
References 33 publications
0
89
0
2
Order By: Relevance
“…28 We have proposed a chemiluminescent means of activating the pharmacological activity of hypericin and its analogs. 29 …”
Section: Introductionmentioning
confidence: 99%
“…28 We have proposed a chemiluminescent means of activating the pharmacological activity of hypericin and its analogs. 29 …”
Section: Introductionmentioning
confidence: 99%
“…A majority of the herb's antidepressant activity have recently been attributed to hyperforin and adhyperforin, and these compounds also possess antibacterial and cell growth inhibitory activity (1)(2)(3)14). The naphthodianthrone compounds, hypericin and its major metabolite pseudohypericin, have been shown to possess potent antiviral and cytotoxic properties upon light exposure (10)(11)(12)15).…”
Section: Introductionmentioning
confidence: 99%
“…Our group has characterized the antiviral activity of hypericin using equine infectious anemia virus (EIAV) as a retroviral model of HIV. [31][32][33][34][35][36][37][38] EIAV is a well-suited model for for studies of antiviral agents effective against HIV since it is an enveloped lentivirus that is structurally, genetically, and antigenically related to HIV. [39][40][41] Our studies have demonstrated that hypericin, in the presence of ambient room light, reduces the infectivity of cell-free stocks of EIAV by 99.99%.…”
Section: Virus Replication and Antiviral Drugsmentioning
confidence: 99%
“…42,43 More recently, we have devised a strategy to place in the proximity of hypericin a chemiluminescent light source so that photodynamic therapy can be extended to all regions of the body. 33 Examination of the structural and chemical basis for light-activated virucidal activity has resulted in new concepts of how these compounds may inactivate the virus. [34][35][36] These studies represent the fruit of a successful interaction of synthetic chemistry with molecular virology and physical chemistry and illustrate how such interactions may lead to novel antiviral therapies.…”
Section: Virus Replication and Antiviral Drugsmentioning
confidence: 99%